Causes and course of climate change and its hydrological consequences in the Greater Poland region in 1951-2020 - Marsz, Andrzej A.; Sobkowiak, Leszek; Styszyńska, Anna; Wrzesiński, Dariusz (Quaestiones Geographicae, 2022)
The paper presents effects of changes in climatic elements in the Greater Poland region (Poland), their causes and consequences for shaping the water balance of this area, copying with the most severe water deficit in Poland. The study period covers 70 years (1951–2020). The research identified an abrupt and significant change in the climate of Greater Poland, which started between 1987 and 1989, concerning not only air temperature but also a wider spectrum of climatic elements. The change in the state of the climate, which covers the entire Atlantic-Eurasian circulation sector, re-sults from a sudden change in the macro-circulation conditions in the middle troposphere (500 hPa). The reason for the change in the mid-tropospheric circulation is an equally abrupt and simultaneous change in the intensity of the ocean heat transport by the North Atlantic thermohaline circulation (NA THC). Climate change observed in Greater Poland is manifested in an increase in sunshine duration (SD) and air temperature, a decrease in relative humidity, a change in the cloud structure, and an increase in the degree of sky coverage. The main, physical reason for an increase in air tempera-ture is a rapid and strong increase in SD in the warm half-years, which began after 1988, and a significant increase in the frequency of positive North Atlantic Oscillation (NAO) phases in winters. The ongoing climate change entails various effects, among which the most important is considered to be hydrological consequences. The water balance of Greater Poland is becoming increasingly unfavourable, mainly as a result of a rapid increase in field evaporation.